Serum phosphate as an additional marker for initiating hemodialysis in patients with advanced chronic kidney disease - Yueh-An Lu; Shen-Yang Lee; Hui-Yi Lin; Yen-Chun Liu; Huang-Kai Kao; Yung-Chang Chen; Ya-Chung Tian; Cheng-Chieh Hung; Chih-Wei Yang; Hsiang-Hao Hsu (Biomedical Journal, 2015)
Background: Reconsidering when to initiate renal replacement therapy (RRT) in patients with chronic kidney disease (CKD) has been emphasized recently. With evolving modern aged and diabetes-prone populations, conventional markers of uremia are not sufficient for determining the optimal timing for dialysis initiation. This retrospective cohort study examined the association between hyperphosphatemia and uremic patients who need RRT registration. Methods: All patients from the department of nephrology in one tertiary medical center in northern Taiwan who had advanced CKD and estimated glomerular filtration rates <8 mL/min/1.73 m2 from July 2009 to May 2013 were enrolled. We reviewed the medical records and collected data on demographics, comorbidities, underlying diseases, duration of nephrology care, use of phosphate binders, and laboratory results. Univariable and multivariable logistic regression models were used to identify factors associated with hemodialysis initiation decision making. Results: During the study period, 209 of 292 patients with advanced CKD were enrolled in hemodialysis program and 83 patients (controls) were not. Univariable analysis indicated that male sex, current smoking, diabetes mellitus, hypertension, coronary artery disease, high serum creatinine level, and high serum phosphate level were associated with initiation of hemodialysis. Multivariable analysis indicated that those with higher serum phosphate level (odds ratio [OR] = 2.4, 95% confidence interval [CI] = 1.6–3.5, p = 1.4 × 10−5) and being in nephrology care for <12 months (OR = 0.4, 95% CI = 0.2–0.8, p = 0.016) tended to be significant markers for hemodialysis initiation. Conclusion: Hyperphosphatemia, in addition to conventional laboratory markers and uremic symptoms, may be a useful marker to determine timing of hemodialysis initiation in patients with advanced CKD.